MORPHOLOGICAL, ANATOMICAL AND CHEMICAL ANALYSES OF AMORPHOPHALLUS PAEONIIFOLIUS AND RELATED TAXA - Elizabeth A. Widjaja; R.N. LESTER (Research Center for Biology, 1987)
A study on the affinity of undescribed taxa of Amorphophallus with A. paeoniifolius and its related species was undertaken using numerical analyses of data derived from preserved and living specimens. The results obtained were compared with the system of classification produced by classical taxonomic methods. The Javanese wild and cultivated forms of Amorphophallus paeoniifolius respectively known locally as